Imagen de hipertrofia bilateral del proceso coronoides mandibular a través de la tomografía computarizada cone-beam - Alves, Nilton [UNESP] (2012)
The hypertrophy of the mandibular coronoid process is a rare condition, progressive and of unknown etiology, characterized by the over development of the coronoid process determining their size increased, resulting in progressive and painful limitation of mouth opening. The mandibular hypomobility is a present symptom in several diseases and associates it to a specific cause requires detailed clinical and imaginologic examination. The cone-beam computed tomography has the potential to provide complementary informations above than conventional radiography. It also has the advantage of eliminate overlaps, provide high resolution image, helping not only in diagnosis, but also in planning the surgical procedure. Here we report a case of male patient, who appeared at the clinic for an evaluation of a trismus. He had no pain, only discomfort for progressive limitation of mouth opening. On physical examination, only a limited mouth opening has been found. Although the movements of laterality and protrusión were posible, they were very limited. Cone-beam computed tomography examination was performed, that showed an image compatible with bilateral hypertrophy of the mandibular coronoid process.